Perioperative concerns in transoral robotic surgery: Initial experience of four cases - Suryakumar Narayanasamy; Puneet Khanna; A P Bhalla; Anil Kumar Singh (Wolters Kluwer Medknow Publications, 2012)
US Food and Drug Administration has recently approved transoral robotic surgery for the treatment of some benign tumors and selected malignant tumors of the head and neck. Robotically-assistance in ear, nose and throat surgery is established and will play an increasingly large role in the future of surgical practice. Anesthesiologists need to modify their management and familiarize themselves with the upcoming robotic procedures to ensure better patient outcomes and improve patient safety.